Corelation Between Uric Acid and Neutrophil Lymphocyte Ratio (NLR) in Controlled and Uncontrolled Type 2 Diabetes Mellitus - Immanuel Situmorang; Jelita Siregar; Santi Syafril (GLOBAL HEALTH SCIENCE GROUP, 2025)
Type 2 diabetes mellitus (DM) is a metabolic disease characterized by chronic hyperglycemia, often linked to metabolic complications and inflammatory conditions. Uric acid and Neutrophil-Lymphocyte Ratio (NLR) are biomarkers of inflammation and oxidative stress in this condition. This study aims to examine the relationship between uric acid and NLR in controlled and uncontrolled type 2 DM patients. Using an analytical observational design with a cross-sectional approach and consecutive sampling, 112 subjects were divided into controlled (HbA1c < 7%) and uncontrolled (HbA1c ≥ 7%) groups. Data were collected from RSUP H. Adam Malik Medan through laboratory tests for whole blood, uric acid, and HbA1c levels. Pearson or Spearman correlation tests were used to assess relationships between variables with a significance level of p < 0.05. Significant demographic differences were found between groups, with higher uric acid and HbA1c levels in the uncontrolled DM group. Positive correlations were observed between uric acid and NLR, as well as uric acid and HbA1c, in both groups. Additionally, a strong positive association between HbA1c and NLR was found in both groups. Uric acid, NLR, and HbA1c are correlated in both controlled and uncontrolled type 2 diabetes mellitus.